Libro De Actas IN-RED 2018: IV Congreso Nacional De Innovación Educativa Y Docencia en Red 2018
DOI: 10.4995/inred2018.2018.8598
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la gamificación en diferentes cursos y tipos de alumno

Abstract: ResumenLa gamificación web abre nuevas oportunidades en la enseñanza, especialmente en materias relacionadas con agricultura donde existe una desmotivación general en el aprendizaje de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Popular online games have shown very interest in students, fomenting the competitivity and superiority of the smartest student of the group (Rajšp et al, 2017). Many works have demonstrated that gaming platforms result pleasant and fun to play, even though many of them do not deliver knowledge, only serve as a tool of reinforcing the knowledge of students (Sola Guirado, Castro García, & González Sánchez, 2018;Stott & Neustaedter, 2014). One of the most popular gamification tools being used in the academic field is Kahoot!, which is a free e-learning platform with more than 30 million users (Bicen & Kocakoyun, 2018).…”
Section: Gamification In Education: Case Of Kahoot!mentioning
confidence: 99%
“…Popular online games have shown very interest in students, fomenting the competitivity and superiority of the smartest student of the group (Rajšp et al, 2017). Many works have demonstrated that gaming platforms result pleasant and fun to play, even though many of them do not deliver knowledge, only serve as a tool of reinforcing the knowledge of students (Sola Guirado, Castro García, & González Sánchez, 2018;Stott & Neustaedter, 2014). One of the most popular gamification tools being used in the academic field is Kahoot!, which is a free e-learning platform with more than 30 million users (Bicen & Kocakoyun, 2018).…”
Section: Gamification In Education: Case Of Kahoot!mentioning
confidence: 99%
“…(Rajšp et al, 2017). Many works have demonstrated that gaming platforms result pleasant and fun to play, even though many of them do not deliver knowledge, only serve as a tool of reinforcing the knowledge of students (Sola Guirado, Castro García, & González Sánchez, 2018;Stott & Neustaedter, 2014). One of the most popular gamification tools being used in the academic field is Kahoot!, which is a free e-learning platform with more than 30 million users (Bicen & Kocakoyun, 2018).…”
Section: Bloom Taxonomymentioning
confidence: 99%